The Links–Gould Invariant as a Classical Generalization of the Alexander Polynomial?. Issue 3 (3rd July 2018) - Kohli, Ben-Michael
ABSTRACT: In this article, we conjecture that the Links–Gould invariant of links, which we know is a generalization of the Alexander–Conway polynomial, shares some of its classical features. In particular, it seems to give a lower bound for the genus of links and to provide a criterion for fibredness of knots. We give some evidence for these two assumptions.